KARAKTERISTIK IKLIM MIKRO DI BAWAH TEGAKAN SENGON-KACANG PANJANG DAN JABON–BUNCIS - Andi Fazlur Agung Anuar; Karyati Karyati (ULIN: Jurnal Hutan Tropis, 2019)
The combination planting of forestry and agriculture plants influence microclimate under tree stand. The objective of this study was to investigate the characteristics of microclimate (air temperature, relative humidity, and light intensity) under stands of sengon (Falcataria moluccana)-long bean (Vigna cylindrica), jabon (Anthocephalus cadamba)-bean (Phaseolus vulgaris), and open area. The measurement of climate elements was conducted three times a day, such as in the morning (06.00-07.00),  at noon (11.00-12.00), and afternoon (17.00-18.00) for 30 days by using Environment meter. The average light intensity were 533.5 lux, 534.3 lux, and 1919.7 lux under stands of sengon-long bean, jabon-bean, and open area. The average temperature under stands of  sengon-long bean was 29.9°C, under jabon-bean was 30.0°C , and in the open area was 31.2°C. The average relative humidity under stands of sengon-long bean, jabon-bean, and open area were 69.5%, 69.3%, and 67.2%, respectively.